Rare bird documentation form for Lesser Black-backed Gull at Lock and Dam 15, 1992 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1992)
Rare bird documentation form for a Lesser Black-backed Gull at Lock and Dam 15 in Davenport in Scott County, IA on January 17, 1992. Epson - sheet feed